Risk factors in pediatric asthmatic patients. Cases and control studies. - Rafael Alejandro Gómez Baute; Yaney Gonzalez Iglesias (Medisur)
Background: Asthma constitutes the first disease among chronic diseases in children. The morbid-mortality promoted to continue being elevated in spite of the new therapies. For this reason it is a disease with high priority for investigation in pediatric ages. Method: A control and case group study was carried out. The samples was composed by 72 asthmatic children from three General Comprehensive doctor offices from Palmira health area located in Cienfuegos Province, Cuba; and a control group of 72 children apparently healthy from the same population. A questionnaire with the different risk variables was elaborated. Odds ratio technique was used to estimate the risk. Results: low weight at birth, family history of asthma, brochiolitis antecedent and the excessive usage of antibiotics in children under 1 year old were the main risks found. Conclusions: It is conclusive that the exposure to home allergen plus a genetic favorable factor, the prematurity, and brochiolitis constituted the most outstanding elements to suffer from asthma in the population studied.